2, 3, 5, 4′‐Tetrahydroxystilbene‐2‐O‐β‐glucoside potentiates self‐renewal of human dental pulp stem cells via the AMPK/ERK/SIRT1 axis. (26th April 2018) - Lin, C.‐Y.; Chin, Y.‐T.; Kuo, P.‐J.; Lee, H.‐W.; Huang, H.‐M.; Lin, H.‐Y.; Weng, I.‐T.; Hsiung, C.‐N.; Chan, Y.‐H.; Lee, S.‐Y.
Abstract: Aim: To evaluate the effect of 2, 3, 5, 4′‐tetrahydroxystilbene‐2‐O‐β‐D‐glucoside (THSG) on cell proliferation and examine the mechanisms of THSG‐enhanced proliferative potential in human dental pulp stem cells (hDPSC). Methodology: After treatment with THSG, hDPSC were collected. Cell viability was determined by MTS assay, while messenger RNA (mRNA) expressions of proliferation and stem cell markers were analyzed using real‐time PCR. Flow cytometry was also conducted to analysis protein expression of stem cell markers. A colony‐forming unit assay of hDPSC was carried out. Cellular telomerase activity was also identified using real‐time PCR. In addition, proliferation‐related proteins involved in the effects of THSG on hDPSC were analyzed by Western blotting. Data were analyzed using one‐way analysis of variance and two‐tailed Student's t ‐test. Results: Cell viability, colony‐forming rates and telomerase activities of hDPSCs were enhanced after THSG treatment. mRNA expressions of proliferation markers (including expressions of NAD+‐dependent histone deacetylase sirtuin 1 ( SIRT1 ), proliferating cell nuclear antigen ( PCNA ), cyclin D1 and ribonucleotide reductase subunit M2 ( RRM2 )) increased significantly after THSG treatment ( P  <   0.05). Treatment with THSG for 3 h significantly augmented SIRT1 protein expression ( P  <   0.05). Furthermore, activities of proliferation‐related proteins (including AMP‐activated protein kinase (AMPK) and extracellular signal‐regulated kinase (ERK) had also significantly increased at 3 h ( P  <   0.05). After THSG treatment, increased gene and protein expressions of pluripotent‐like stem cell markers (including NANOG, OCT4, and SOX2) were observed. Conclusions: 2, 3, 5, 4′‐Tetrahydroxystilbene‐2‐O‐β‐glucoside treatment enhanced the renewal ability and proliferative potential of hDPSCs via the AMPK/ERK/SIRT1 axis, which may provide a novel autogenic cell‐based therapeutic strategy in regenerative dentistry.